1993
DOI: 10.3109/00365529309098288
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Helicobacter pylori Reduces the Rate of Rebleeding in Peptic Ulcer Disease

Abstract: Eradication of H. pylori infection reduces the rate of ulcer recurrence and rebleeding in complicated ulcer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
1
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(116 citation statements)
references
References 19 publications
3
105
1
6
Order By: Relevance
“…14 Shipnen et al 1992, Grahm et al 1991 reported that H. pylori infection more common in lower socioeconomic status and author have reported similar results in this study amongst patients with perforation H. pylori infection is the same across the socioeconomic status (50% for lower socioeconomic group, 56% in the rest). 15,16 The stool antigen test for detection of H. pylori was carried out in 20 out of 75 patients with perforated peptic ulcer and it was found to be negative for H. pylori for all the 20 patients. The sensitivity of stool antigen test in simple ulcer as reported in literature is in range of 88-100%.…”
Section: Resultsmentioning
confidence: 99%
“…14 Shipnen et al 1992, Grahm et al 1991 reported that H. pylori infection more common in lower socioeconomic status and author have reported similar results in this study amongst patients with perforation H. pylori infection is the same across the socioeconomic status (50% for lower socioeconomic group, 56% in the rest). 15,16 The stool antigen test for detection of H. pylori was carried out in 20 out of 75 patients with perforated peptic ulcer and it was found to be negative for H. pylori for all the 20 patients. The sensitivity of stool antigen test in simple ulcer as reported in literature is in range of 88-100%.…”
Section: Resultsmentioning
confidence: 99%
“…Exaggerated mealstimulated gastrin release was shown to be related to H. pylori infection and reversed following cure of the infection. 27,28 The inability to demonstrate a relationship between gastrin secretion or acid secretion and H. pylori infection, and the Âźnding that the parietal cell mass did not reliably fall following a cure of the infection, eliminated the hypothesis that the gastrin was responsible, either directly or indirectly, for the trophic eect seen in duodenal ulcer disease. 29±32 Overall, these observations provided the basic knowledge of studies required in order to understand how to evaluate H. pylori-related perturbations in gastric function (Table 2).…”
Section: Secretionsmentioning
confidence: 99%
“…15 About 1 in 10 duodenal ulcers bleed for reasons that remain unclear, but of critical importance is the fact that eradication of H. pylori dramatically reduces the occurrence of rebleeding from both duodenal and gastric ulcers. 16 Curiously, a similar beneficial impact has not been demonstrated for H. pylori eradication in the management of peptic ulcer perforation. 17 The prevalence of H. pylori-negative peptic ulcer disease appears to be on the increase.…”
mentioning
confidence: 99%